Enterprise J2ME™: Developing Mobile Java™ Applications - Yuan, Michael (Pearson, 2003)
Industrial-strength J2ME™ for enterprise developers, architects, and decision-makers J2ME offers an extraordinarily flexible and robust platform for developing mobile applications with enterprise-class performance, reliability, and value. Now, leading mobile developer Michael Yuan covers every aspect of building industrial-strength applications with J2ME: design, architecture, tools, processes, business issues, and more. Yuan introduces innovations that make the platform even more powerful, ranging from new J2ME profiles and wireless messaging APIs to mobile databases and web services tools. These innovations allow existing Java™ developers (especially J2EE™ developers) to leverage their skills and add mobility to enterprise applications. Yuan also presents more than a dozen complete sample applications-including the application that earned him the grand prize in Nextel, Sun, and Motorola's nationwide wireless developer contest. Coverage includes: Patterns and best practices for building end-to-end mobile applications Emerging mobile "killer applications": driving productivity and cost reduction "Smart client" applications: architecture and construction Advanced HTTP techniques for authentication and session tracking Overcoming hardware and network limitations Leading-edge mobile enterprise messaging techniques Mobile databases and synchronization engines XML and mobile web services, including the J2ME Web Services Optional Package New options for mobile security in the enterprise.